Eco-Friendly Facing Brick Using Waste Materials and Method for Manufacturing the Same
Patent Information
- Application Number
- KR1020260093544
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2026-05-22
- Publication Date
- 2026-09-01
- Estimated Expiration
- 2046-05-22
Smart Images

Figure 112026062845276-PAT00004_ABST
Abstract
Description
Technology Field
[0001] This invention relates to an eco-friendly plaster brick and a method for manufacturing the same, wherein the brick is manufactured using waste materials derived from power plant byproducts and can secure excellent water absorption and compressive strength even at low firing temperatures. Background Technology
[0002] Clay bricks are bricks made by mixing, kneading, molding, drying, and firing inorganic clay raw materials generated from rocks that have weathered or decomposed over a long period of time.
[0003] Plastering bricks are bricks fired using clay or similar materials as the main raw material, and perforated bricks are bricks manufactured such that the effective cross-sectional area of the load-bearing surface is 50% or more of the total cross-sectional area, and also include bricks fired in a molten state with glaze or similar materials on the surface.
[0004] Clay bricks are widely used as interior and exterior building materials, plastering bricks, and landscaping bricks, and are generally manufactured by molding clayey raw materials and then firing them. In particular, perforated clay bricks are applied in various construction fields because the multiple through holes formed inside improve lightweight properties, thermal insulation, and ease of installation.
[0005] Meanwhile, the manufacturing process of clay bricks generally requires high firing temperatures and long firing times, leading to persistent issues regarding high fuel consumption and increased manufacturing costs and carbon emissions. Consequently, technologies have recently been proposed to reduce fuel consumption and improve resource recyclability by utilizing waste materials, such as coal ash, as raw materials for clay bricks.
[0006] The above coal ash refers to an inorganic byproduct generated after the combustion of coal fuel in a coal-fired power plant. Depending on the location where it is collected after combustion, this coal ash can be classified into bottom ash and fly ash. The above bottom ash refers to coal ash of relatively coarse particles that are attached to the furnace walls, superheaters, or reheaters of a boiler and fall to the bottom of the boiler due to their own weight; generally, the particle size may be about 1 to 2.5 mm or larger. Additionally, the above fly ash refers to coal ash of fine particles that are collected by a hopper and an electrostatic precipitator located at the bottom of an economizer or air preheater.
[0007] However, excessive use of unrefined fly ash can lead to the formation of excessive pores and a decrease in structural density during the firing process, which may result in increased water absorption and reduced compressive strength of clay bricks. In particular, for plaster bricks with cylindrical perforations within the body, securing compressive strength is relatively difficult; therefore, the problems of increased water absorption and reduced compressive strength caused by the use of unrefined fly ash may become even more pronounced.
[0008] Accordingly, there is a demand for technology that can stably secure physical properties such as water absorption rate and compressive strength while reducing fuel consumption. Prior art literature
[0009] Registered Patent No. 10-1138425 (Registered on April 13, 2012) The problem to be solved
[0010] This invention aims to provide an eco-friendly plaster brick and a method for manufacturing the same, which can reduce fuel consumption in the plaster brick manufacturing process by improving the waste material utilization rate to over 40 weight percent while securing excellent compressive strength and low water absorption, and reducing the average firing temperature and actual heating time. means of solving the problem
[0011] The first embodiment of the invention is an eco-friendly brick manufactured by mixing a mixture of soil and water, undergoing a molding process, and then drying and firing, wherein the mixture of soil comprises clay, weathered granite, kaolin, and waste materials, and the waste materials comprise unrefined fly ash, refined fly ash, an incinerated ash-based solidifying agent, and feldspar powder, and the eco-friendly brick has a plurality of cylindrical perforations (110) formed inside the body (10) of the eco-friendly brick.
[0012] The above perforated portion (110) is formed so that the upper and lower parts of the eco-friendly plaster brick body (10) penetrate, and the effective area of the load-bearing surface of the eco-friendly plaster brick excluding the perforated portion (110) is 70% or more of the total surface area.
[0013] The above mixture contains 15-30% by weight of clay, 10-30% by weight of weathered granite, 5-15% by weight of kaolin, and 40-49% by weight of waste material.
[0014] The above unrefined fly ash contains 5 weight percent or more of unburned carbon, and the above refined fly ash contains less than 5 weight percent of unburned carbon.
[0015] The above-mentioned incineration ash-based solidifying agent comprises dihydrate gypsum, hemihydrate gypsum, and an alumina-based inorganic binder, wherein the dihydrate gypsum is one or more selected from the group consisting of Gypsum stone (CAS No. 13397-24-5), desulfurization gypsum, and recycled gypsum, the hemihydrate gypsum is one or more selected from the group consisting of Calcium sulfate hemihydrate (CAS No. 10034-76-1), α-hemihydrate gypsum, β-hemihydrate gypsum, and calcined gypsum, and the alumina-based inorganic binder is one or more selected from the group consisting of Cement bonded alumina (CAS No. 65997-16-2), calcium aluminate cement, alumina cement, high alumina cement, and calcium aluminate.
[0016] The above-mentioned incineration ash-based solidifying agent comprises 90-98% by weight of dihydrate gypsum, 1-5% by weight of hemihydrate gypsum, and 1-5% by weight of alumina-based inorganic binder.
[0017] A second embodiment of the present invention is a method for manufacturing an eco-friendly plaster brick comprising: a mixing step (S100) of preparing a clay mixture by mixing water with a mixture of clay, weathered granite, kaolin, and waste materials; a molding step (S200) of extruding the clay mixture under vacuum to form a plurality of cylindrical perforations (110) inside an eco-friendly plaster brick body (10); a drying step (S300) of drying the molded clay mixture; and a firing step (S400) of manufacturing an eco-friendly plaster brick by heating the dried clay molded product in a tunnel kiln.
[0018] In the above molding step (S200), the perforations (110) formed inside the brick body (10) are formed in three such that the upper and lower parts of the brick body (10) are penetrated, and the clay mixture can be molded so that the effective cross-sectional area of the load-bearing surface excluding the perforations (110) is 70% or more of the total cross-sectional area.
[0019] Between the drying step (S300) and the firing step (S400), a glazing step (S350) for applying engobe to the surface of the dried clay molded product may be further included.
[0020] The above firing step (S400) is performed sequentially in the direction in which the clay molded product is transported in the tunnel kiln, in the direction of the preheating step (S410), the main firing step (S420), and the cooling step (S430). In the preheating step (S410), the clay molded product is preheated using the heat generated in the main firing step (S420) without performing separate heating. The main firing step (S420) includes a heating section and a non-heating section. In the heating section, heating is performed so that the average firing temperature of the heating section becomes 1070~1100℃. In the non-heating section, no heating is performed. The firing reaction of the clay molded product proceeds by the combustion heat of the unburned carbon contained in the unrefined fly ash to form an eco-friendly plaster brick. In the cooling step (S430), the manufactured eco-friendly plaster brick is cooled to room temperature.
[0021] In the above drying step (S300), waste heat generated in the above cooling step (S430) is circulated to a drying chamber where the drying step (S300) is performed, and drying of the clay molded product can be performed.
[0022] The above waste material comprises 32-38% by weight of unrefined fly ash, 3-8% by weight of refined fly ash, 1-5% by weight of a solidifying agent, and 1-3% by weight of feldspar powder, based on 100% by weight of the mixed soil.
[0023] In the above waste material, the FAR value expressed by [Equation 1] can be 7.5 to 20.
[0024] Effects of the invention
[0025] The eco-friendly plaster brick of this invention can improve the recyclability of waste materials by using waste materials including refined fly ash, unrefined fly ash, an incineration ash-based solidifying agent, and feldspar powder. In particular, the eco-friendly plaster brick of this invention can contain 40 weight percent or more of waste materials, making it eco-friendly and improving resource recyclability, and satisfying the Green Technology Certification standards.
[0026] In addition, this invention utilizes the self-heating of unburned carbon contained in unrefined fly ash to maintain the firing temperature of the clay molded product even in the non-heating section during the main firing step (S420). Accordingly, the average firing temperature and actual heating time are reduced, thereby reducing fuel consumption by more than 40%.
[0027] Furthermore, by using refined fly ash together, this invention can complement the uniformity of fly ash components within the mixture without excessively inhibiting the self-heating effect of unrefined fly ash. Accordingly, this invention alleviates blackness, color variation, and pore non-uniformity, and improves the density and uniformity of the brick structure after firing, thereby stably ensuring the appearance quality, water absorption rate, and compressive strength of eco-friendly plaster bricks.
[0028] In addition, the energy efficiency of the manufacturing process can be further improved by recycling waste heat generated during the calcination process into the drying process.
[0029] Furthermore, the eco-friendly plaster brick of this invention, by including refined fly ash and an incinerated ash-based solidifying agent, can stably secure structural density even under low firing temperature conditions, and accordingly, can exhibit excellent physical properties such as an absorption rate of 9% or less and a compressive strength of 26 MPa or more. This means that it can secure excellent quality stability and structural stability that not only satisfy the standards of KS L 4201 but also exceed them. In particular, the eco-friendly plaster brick of this invention has the advantage of securing excellent compressive strength and durability despite being a porous brick with multiple through holes formed inside.
[0030] Furthermore, by including unrefined fly ash, refined fly ash, and incineration ash-based solidifying agents within an optimal content range in the waste materials used in the eco-friendly plaster bricks of this invention, excellent compressive strength and low water absorption can be reliably secured, efflorescence can be suppressed, and fuel consumption during the firing process can be reduced. In addition, the drying time of the clay molded product can be shortened, and cracking, sagging, or shape deformation that may occur during the drying process can be suppressed.
[0031] Furthermore, the eco-friendly plaster brick of this invention can achieve a balanced combination of the self-heating effect caused by unrefined fly ash and the tissue homogenization effect caused by refined fly ash by adjusting the FAR (Fly ash ratio) value, calculated from the content of unrefined fly ash and refined fly ash, to an optimal range. Accordingly, the water absorption rate and compressive strength of the eco-friendly plaster brick can be further improved.
[0032] Thus, this invention can provide an eco-friendly plaster brick that simultaneously satisfies eco-friendliness, economic efficiency, and quality stability, as it can secure physical properties such as water absorption rate and compressive strength along with the fuel saving effect resulting from the utilization of waste materials. Brief explanation of the drawing
[0033] FIG. 1 is a perspective view of an eco-friendly plaster brick according to a first embodiment of the present invention. FIG. 2 is a flowchart illustrating a method for manufacturing eco-friendly plaster bricks according to a second embodiment of the present invention. Specific details for implementing the invention
[0034] Before describing the preferred embodiments of this invention in detail below, it should be noted that the terms and words used in this specification and claims should not be interpreted as being limited to their ordinary or dictionary meanings, but should be interpreted in a meaning and concept consistent with the technical spirit of this invention.
[0035] Throughout this specification, when a part is described as “comprising” a certain component, this means that, unless specifically stated otherwise, it does not exclude other components but may include additional components.
[0036] Throughout this specification, “%” used to indicate the concentration of a particular substance means (weight / weight)% for solid / solid, (weight / volume)% for solid / liquid, and (volume / volume)% for liquid / liquid, unless otherwise noted.
[0037] In each step, identification codes are used for convenience of explanation and do not describe the order of the steps; unless the context clearly indicates a specific order, the steps may be performed differently from the specified order. That is, the steps may be performed in the same order as specified, substantially simultaneously, or in the reverse order.
[0038] The present invention will be described in detail with reference to the embodiments and drawings. These embodiments are presented merely as examples to explain the invention more specifically, and it will be obvious to those skilled in the art that the scope of the invention is not limited by these embodiments.
[0039] Furthermore, unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which this invention pertains, and in the event of a conflict, the description in this specification, including the definitions, shall prevail.
[0040] The first embodiment of this invention is an eco-friendly brick manufactured by mixing a mixture of soil and water, undergoing a molding process, and then drying and firing, wherein the mixture of soil comprises clay, weathered granite, kaolin, and waste materials, and the waste materials comprise unrefined fly ash, refined fly ash, an incinerated ash-based solidifying agent, and feldspar powder, and the eco-friendly brick has a plurality of cylindrical perforations (110) formed inside the body (10) of the eco-friendly brick.
[0041] The manufacturing of conventional clay bricks requires a high average firing temperature and long heating times, which has resulted in high fuel consumption during the manufacturing process and increased manufacturing costs and carbon emissions. Additionally, when only unrefined fly ash is used as waste material, excessive pores may be formed or structural uniformity may be reduced due to the combustion of unburned carbon during the firing process, which has the disadvantage of increasing the water absorption rate of the clay brick or reducing its compressive strength. In particular, in the case of plaster bricks containing perforations (110), it is relatively difficult to secure strength due to the cylindrical perforations (110), which can further reduce structural stability.
[0042] On the other hand, the eco-friendly plaster brick of this invention can reduce the average firing temperature and fuel consumption through the self-heating effect of unrefined fly ash, and the sintering reaction of the clay brick can be stably induced even at low firing temperatures by refined fly ash and a solidifying agent, thereby improving the density and strength of the structure. Accordingly, while increasing the waste material utilization rate to over 40 weight percent, it is possible to secure excellent compressive strength and water absorption rates exceeding the standards of KS L 4201. In addition, since excellent physical properties can be secured even under low firing temperature conditions, fuel consumption in the clay brick manufacturing process can be reduced.
[0043] The perforations (110) formed inside the above-mentioned eco-friendly brick body (10) are formed in three such that the upper and lower parts of the brick body (10) penetrate each other, and the effective cross-sectional area of the load-bearing surface excluding the perforations (110) can be formed to be 70% or more of the total cross-sectional area.
[0044] The above eco-friendly plastering brick may have dimensions of length, width, and thickness of the eco-friendly brick body (10) of 190*90*57mm.
[0045] The above mixture contains 15-30% by weight of clay, 10-30% by weight of weathered granite, 5-15% by weight of kaolin, and 40-49% by weight of waste material.
[0046] The clay mixture can be prepared by mixing 100 parts by weight of mixed soil and 15 to 20 parts by weight of water. If the amount of water is less than the above range, the plasticity and fluidity of the clay mixture decrease, making it difficult to mix the raw materials uniformly and potentially reducing extrusion moldability. On the other hand, if the amount of water exceeds the above range, drying shrinkage increases, which may cause cracking, warping, or through-hole deformation, and consequently, dimensional stability and compressive strength may decrease after firing.
[0047] The above clay is mixed with water to impart plasticity and moldability to the clay mixture, and forms the basic framework of the clay brick through molding and firing processes.
[0048] The clay may be included in the mixture at 15 to 30 weight percent, preferably at 20 to 30 weight percent. If the clay is included below the above range, the plasticity of the clay mixture decreases, resulting in reduced moldability, which may cause cracking or breakage of the molded clay mixture. On the other hand, if the clay is included above the above range, the waste content is relatively reduced, which may lower the waste utilization rate and fuel saving effect, and drying shrinkage or firing shrinkage may increase, leading to reduced dimensional stability. The above dimensional stability refers to the characteristic of the clay brick maintaining its initial shape and dimensions stably even after the drying and firing processes.
[0049] The above-mentioned sand is a sandy inorganic raw material formed by the weathering of rocks such as granite. Since the above-mentioned sand has relatively coarser particles and lower plasticity compared to clay, it can reinforce the framework of the eco-friendly plaster brick of this invention to mitigate shrinkage occurring during the drying and firing processes and improve durability.
[0050] The above-mentioned sand may be included in the mixture at a weight of 12 to 30%, preferably 12 to 21%. If the sand is included in an amount less than the above range, the effect of inhibiting drying shrinkage and firing shrinkage is not sufficiently exerted, and the dimensional stability and crack resistance of the clay molded article may be reduced. On the other hand, if the sand is included in an amount exceeding the above range, the plasticity and bonding strength of the clay mixture decrease, which may reduce extrusion moldability, and it may be difficult to form a dense structure of the clay brick after firing, which may increase the water absorption rate or reduce the compressive strength.
[0051] The above kaolin is a fine inorganic raw material containing kaolinite ((Al2Si2O5(OH)4)) as its main component, and has a lower impurity content and a higher Al2O3 content compared to clay. Incorporating such kaolin into the eco-friendly plaster brick of this invention can improve the structural density, compressive strength, and quality stability of the clay mixture after firing.
[0052] The above kaolin may be included in the mixture at 5 to 15 weight percent, preferably at 8 to 13 weight percent. If the kaolin is included in an amount less than the above range, the water absorption rate of the eco-friendly plaster brick may increase or the compressive strength may decrease. On the other hand, if the kaolin is included in an amount exceeding the above range, the plasticity and extrusion moldability of the clay mixture may decrease.
[0053] The above waste material refers to a material recycled from inorganic by-products or residues generated in industrial processes, power generation processes, or incineration processes, and the above waste material may include unrefined fly ash, refined fly ash, incineration ash-based solidifying agents, and feldspar powder.
[0054] In this way, by using waste materials in the manufacture of the eco-friendly plaster bricks of this invention, excellent water absorption and compressive strength can be secured even under low-temperature firing conditions through the mutually complementary action of refined fly ash, unrefined fly ash, incinerated ash-based solidifying agent, and feldspar powder. In addition, by using 40 weight percent or more of waste materials, the Green Technology Certification standards can be satisfied.
[0055] The waste material of this invention may be included in the above-described mixture at a weight of 40 to 49 percent. If the waste material is included in an amount less than the above range, the waste material utilization rate may not be sufficiently secured, which may reduce the recycling effect and eco-friendliness of inorganic waste material, and it may be difficult to satisfy the waste material utilization rate requirements demanded by environmental labels or green technology-related certifications. In addition, the fuel consumption reduction effect and the absorption rate and compressive strength improvement effect caused by unrefined fly ash, refined fly ash, and solidification agents may be reduced.
[0056] On the other hand, if waste materials are included in excess of the above range, the relative content of basic raw materials such as clay, weathered granite, and kaolin decreases, which may reduce the plasticity and extrusion moldability of the clay mixture. In addition, excessive pore formation, black hearts, color deviation, or uneven texture may occur during the firing process, which may lead to an increase in the water absorption rate of the eco-friendly plaster brick and a decrease in compressive strength.
[0057] The above unrefined fly ash is fly ash that contains a relatively large amount of unburned carbon among the fly ash generated after the combustion of coal fuel. For example, the above unrefined fly ash may have an average particle size of 25 to 30 μm and an unburned carbon content of 5 weight% or more.
[0058] The unburned carbon contained in the above unrefined fly ash is burned during the firing stage and acts as a self-heating source within the clay molded product. Accordingly, since the amount of heat that must be supplied by external fuel is reduced, the average firing temperature and actual heating time of the main firing stage (S420) can be lowered, thereby reducing fuel consumption in the clay brick manufacturing process.
[0059] The above unrefined fly ash is based on 100 weight percent of the mixed soil and is used for waste materials. 32~38 It may be included in weight percent. If the content of unrefined fly ash is below the above range, the self-heating effect is insufficient, and the fuel consumption reduction effect may be reduced. On the other hand, if unrefined fly ash is included in excess of the above range, excessive pore formation may occur due to increased combustion of unburned carbon, which may reduce structural density; consequently, the water absorption rate may increase and compressive strength may decrease. Additionally, black hearts, color deviations, or surface defects may occur.
[0060] The purified fly ash mentioned above refers to fly ash generated after the combustion of coal fuel from which at least some of unburned carbon, coarse particles, magnetic particles, or foreign substances have been removed. For example, the purified fly ash may have an average particle size of 10 to 20 μm and an unburned carbon content of less than 5 weight%. The purified fly ash may be produced through at least one of the processes of classification, sieving, air classification, flotation separation, magnetic separation, washing, sedimentation separation, or drying, but is not limited thereto.
[0061] The refined fly ash mentioned above can improve blackness and color variations that may occur when using only unrefined fly ash. In particular, since the refined fly ash has a smaller average particle size, superior uniformity, and lower unburned carbon content compared to unrefined fly ash, it disperses more uniformly within the clay mixture, thereby mitigating localized pore formation and structural non-uniformity. Consequently, the structural uniformity and density of eco-friendly plaster bricks are improved, and this can contribute to reduced water absorption and increased compressive strength.
[0062] Furthermore, the refined fly ash can prevent the localized formation of moisture or salt migration pathways during the drying process by supplementing the uniformity of the fly ash components within the mixing soil. Accordingly, it can suppress the occurrence of efflorescence, which occurs when alkali or salt components within the brick or raw materials migrate to the surface via moisture transport and subsequently precipitate. In this way, the refined fly ash can improve the appearance quality of eco-friendly plaster bricks and prevent a decline in long-term durability and stain resistance caused by moisture or salt migration pathways.
[0063] In addition, the refined fly ash may contain inorganic oxide components including SiO2, Al2O3, Fe2O3, and CaO, and can assist the firing reaction together with an incinerated ash-based solidifying agent during the firing process. Accordingly, the refined fly ash can improve the structural density of eco-friendly plaster bricks even at low firing temperatures, thereby reducing water absorption and increasing compressive strength.
[0064] The above-mentioned refined fly ash may be included in the waste material at a weight of 3 to 8% based on 100% by weight of the mixed soil. If the refined fly ash is included in excess of the above range, the mitigating effect of excessive pore formation, black heart, and color deviation caused by unrefined fly ash is reduced, and the density of the structure is not sufficiently secured at low firing temperatures, which may lead to an increase in water absorption or a decrease in compressive strength. On the other hand, if the refined fly ash is included in excess of the above range, the plasticity and extrusion moldability of the clay mixture are reduced, and the self-heating effect caused by unrefined fly ash is relatively reduced, which may lead to an increase in fuel consumption.
[0065] As such, the waste material of this invention comprises both unrefined fly ash and refined fly ash, thereby simultaneously securing the self-heating effect of the unrefined fly ash and the tissue densification effect of the refined fly ash. Accordingly, it is possible to simultaneously achieve the effects of reducing fuel consumption, decreasing water absorption, and improving compressive strength of eco-friendly plaster bricks.
[0066] At this time, it is preferable that the waste material contains unrefined fly ash and refined fly ash such that the FAR value expressed by Formula 1 below is 7.5 to 20, more preferable that it is 12.5 to 17.5, and most preferable that it is 11 to 14. When the FAR value is 7.5 to 20, it is possible to maintain the self-heating effect caused by unburned carbon contained in the unrefined fly ash while simultaneously securing the pore structure control and tissue densification effects provided by the refined fly ash. Accordingly, it is possible to reduce fuel consumption in the firing process while mitigating excessive pore formation, black hearts, and color deviations caused by the use of unrefined fly ash. In addition, it is possible to reduce the water absorption rate of eco-friendly plaster bricks and improve their compressive strength.
[0067]
[0068] If the above FAR value is below the above range, the relative proportion of refined fly ash decreases, which may reduce the uniformity of the fly ash component in the mixture. On the other hand, if the above FAR value exceeds the above range, the self-heating effect caused by unburned carbon is weakened, which may reduce sufficient sintering reaction and tissue densification. As a result, the effect of improving water absorption and compressive strength may be reduced.
[0069] The above-mentioned incineration ash-based solidifying agent may include dihydrate gypsum, hemihydrate gypsum, and alumina-based inorganic binders derived from coal-fired power generation byproducts or incineration residues. Additionally, the above-mentioned incineration ash-based solidifying agent may further include flux components such as lime-based components and alkali-based components depending on the origin of the raw materials or the manufacturing process.
[0070] The above-mentioned incinerated ash-based solidifying agent promotes the sintering reaction of the clay mixture during the firing process, thereby improving the structural density of eco-friendly plaster bricks even at low firing temperatures. Consequently, since excellent water absorption and compressive strength can be secured even at low firing temperatures, fuel consumption during the firing process can be reduced.
[0071] In addition, the above-mentioned incineration ash-based solidifying agent may further include flux components to promote the formation of a liquid or glassy phase during the firing process of the clay mixture. Accordingly, the bonding between raw material particles is strengthened even under low-temperature firing conditions, and the structural density, compressive strength, and water absorption characteristics of the eco-friendly plaster brick can be improved.
[0072] Furthermore, even if the clay mixture contains trace amounts of heavy metals or harmful components, the heavy metals or harmful components can be trapped within the glassy phase or inorganic binder phase formed during the firing process, thereby suppressing the leaching of the heavy metals or harmful components.
[0073] Meanwhile, the above-mentioned incinerated ash-based solidifying agent may react with clay, kaolin, and fly ash components during the firing process to contribute to the formation of inorganic bonding structures or mineral phases. For example, the above-mentioned incinerated ash-based solidifying agent may contribute to the formation of at least one of mullite, anorthite, or gehlenite mineral phases, and such inorganic bonding structures or mineral phases can improve the compressive strength of eco-friendly plaster bricks.
[0074] In addition, the above-mentioned incineration ash-based solidifying agent can improve drying stability by reacting with moisture contained in the clay mixture during the mixing and drying process. Accordingly, the clay molded product can maintain a state in which cracking, sagging, or shape deformation is suppressed even during a relatively short drying time, and as a result, the drying time can be shortened. For example, the time required to dry the clay molded product to a moisture content of about 1 weight percent can be shortened from the conventional about 100 to 105 hours to about 84 to 86 hours. Therefore, the present invention can improve the productivity and energy efficiency of the manufacturing process by reducing the drying process time.
[0075] The above-mentioned incineration ash-based solidifying agent may be included in the waste material at a weight of 1 to 5% based on 100% by weight of the mixed soil. If the incineration ash-based solidifying agent is included below the above range, the firing temperature increases, leading to increased fuel consumption and a decrease in the water absorption rate and compressive strength of the eco-friendly plaster brick. Additionally, the time required for drying the clay molded product increases, which may reduce process efficiency. On the other hand, if the incineration ash-based solidifying agent is included in excess of the above range, expansion, cracking, warping, or pore non-uniformity may occur during the firing process due to the excessive use of gypsum-based or alumina cement-based components. Consequently, the water absorption rate may increase or the compressive strength may decrease, and the appearance quality may deteriorate due to surface defects or efflorescence.
[0076] The aforementioned dihydrate gypsum is a gypsum-based raw material that forms the main framework of the incineration ash-based solidifying agent. The dihydrate gypsum assists in the formation of bonding structures between raw material particles within the clay mixture and can improve the structural stability of the clay molded product. Furthermore, the dihydrate gypsum works in conjunction with hemihydrate gypsum and alumina-based inorganic binders to suppress the occurrence of cracks during the drying process of the clay molded product and can improve the structural stability of the eco-friendly plaster brick after firing.
[0077] The above-mentioned dihydrate gypsum may be one or more selected from the group consisting of Gypsum stone (CAS No. 13397-24-5), desulfurized gypsum, and recycled gypsum, and preferably, Gypsum stone may be used.
[0078] The above-mentioned dihydrate gypsum may be included in an amount of 90 to 98 weight percent based on 100 weight percent of the total incineration ash-based solidifying agent. If the content of dihydrate gypsum is below the above range, the effect of improving bonding strength between raw material particles of the clay mixture and improving structural stability may not be sufficient. On the other hand, if the content of dihydrate gypsum exceeds the above range, the relative content of hemihydrate gypsum and alumina-based inorganic binder becomes insufficient, which may reduce the effect of improving drying stability and strength after firing.
[0079] The above hemihydrate gypsum reacts with moisture contained in the clay mixture to improve the initial bonding strength between the raw material particles of the clay mixture and can suppress cracking, sagging, or breakage of the clay molded product during the drying process.
[0080] The above hemihydrate may be one or more selected from the group consisting of calcium sulfate hemihydrate (CAS No. 10034-76-1), α-hemihydrate gypsum, β-hemihydrate gypsum, and calcined gypsum, and preferably, calcium sulfate hemihydrate may be used.
[0081] The hemihydrate gypsum may be included in an amount of 1 to 5 weight percent based on 100 weight percent of the total incineration ash-based solidifying agent. If the hemihydrate content is below the above range, the drying stability and shape retention of the clay molded article may be reduced. On the other hand, if the hemihydrate gypsum content exceeds the above range, the reaction with moisture proceeds excessively, which may reduce the workability of the clay mixture or cause drying cracks, dimensional deviations, or warping after firing.
[0082] The above alumina-based inorganic binder can be added together with dihydrate gypsum and hemihydrate gypsum to supplement bonding strength and structural stability.
[0083] The above alumina-based inorganic binder may be one or more selected from the group consisting of cement-bonded alumina (CAS No. 65997-16-2), calcium aluminate cement, alumina cement, high-alumina cement, and calcium aluminate, and preferably cement-bonded alumina may be used.
[0084] The above alumina-based inorganic binder may be included in an amount of 1 to 5 weight percent based on 100 weight percent of the total incineration ash-based solidifying agent. If the content of the alumina-based inorganic binder is below the above range, the effect of supplementing the bonding strength is insufficient, and the strength and structural stability of the clay molded product may be reduced. On the other hand, if the content of the alumina-based inorganic binder exceeds the above range, local differences in densification or shrinkage may occur during the firing process, and consequently, warping, dimensional deviation, or deformation of the perforations may occur in eco-friendly plaster bricks having a porous structure.
[0085] The above feldspar powder is a feldspar-based inorganic powder derived from by-products of coal-fired power generation or process by-products. The above feldspar powder can act as a flux during the firing process of the clay mixture, causing a portion of the clay mixture to soften or partially melt. Accordingly, the voids between clay, weathered granite, kaolin, and fly ash particles are reduced and the inter-particle bonding is strengthened, thereby reducing the porosity of the eco-friendly plaster brick and improving the structural density, compressive strength, and water absorption rate.
[0086] The above feldspar powder may be included in the waste material at a weight of 1 to 3% based on 100% by weight of the mixed soil. If the feldspar powder is included below this range, the fluxing action may not occur sufficiently, which may reduce the structural density of the eco-friendly plaster brick. On the other hand, if the feldspar is included in excess of this range, excessive liquid formation due to melting or softening during the firing process may occur, leading to warping, shrinkage deviation, deformation of through holes, or pore non-uniformity. In particular, in bricks having a perforated structure, the shape stability around the through holes may be reduced.
[0087] Accordingly, the eco-friendly plaster brick of this invention is manufactured by preparing a clay mixture by mixing clay, weathered granite, kaolin, waste materials, and water within the aforementioned range, and then undergoing molding, drying, and firing steps.
[0088] In addition, the harmful component content of the eco-friendly clay brick of this invention must satisfy the criteria of Section 4.2 of the “Environmental Labeling Standards” (EL 745).
[0089] At this time, the eco-friendly plaster brick may further include engobe on the brick surface as needed. The engobe is a surface treatment component that improves the surface color, texture, aesthetics, and appearance uniformity of the eco-friendly plaster brick by being applied to the surface of a dried clay molded product and then fired.
[0090] The above-mentioned engobe can be applied in the form of an engobe composition comprising engobe raw material solids and water. The above-mentioned engobe composition may be in the form of a slurry in which the engobe raw material solids are dispersed in water, and may be applied to the surface of a dried clay molded article. The above-mentioned engobe composition may bond to or become integrated with the surface of the clay molded article during the firing process, thereby improving the surface quality of the eco-friendly plaster brick.
[0091] The above-mentioned engobe may be selected in various ways depending on color or texture, and may include, for example, at least one of blue engobe, white engobe, gray engobe, brown engobe, black engobe, or red engobe. However, the types of the above-mentioned engobe are not limited thereto, and engobe having various colors or textures may be used depending on the application and exterior design of the eco-friendly plaster brick.
[0092] The above-mentioned engobe can be applied in an amount of 0.1 to 0.7 weight percent based on 100 weight percent of the mixed soil. If the engobe is applied in an amount less than the above range, the above-mentioned effect does not occur sufficiently, and if the engobe is applied in an amount exceeding the above range, peeling, cracking, lifting, or surface defects of the engobe may occur during the firing process.
[0093] A second embodiment of the present invention is a method for manufacturing an eco-friendly plaster brick, comprising: a mixing step (S100) of preparing a clay mixture by mixing water with a mixture of clay, weathered granite, kaolin, and waste materials; a molding step (S200) of extruding the clay mixture under vacuum to form a plurality of cylindrical perforations (110) inside an eco-friendly plaster brick body (10); a drying step (S300) of drying the molded clay mixture; and a firing step (S400) of manufacturing an eco-friendly plaster brick by heating the dried clay molded product in a tunnel kiln.
[0094] The above mixing step (S100) is a step of preparing a clay mixture by mixing a mixture of clay, weathered granite, kaolin, and waste materials with water, and by mixing the mixture of clay and water, a clay mixture having plasticity and viscosity suitable for extrusion molding can be prepared.
[0095] Since the details regarding the above-mentioned mixing soil and clay mixture are identical to those described in the first embodiment of this invention, any overlapping details are omitted below.
[0096] The molding step (S200) is a step of extruding the clay mixture to form a clay molded article having the shape of an eco-friendly plaster brick. The molding step (S200) can be performed in a vacuum state, and vacuum extrusion molding can remove air inside the clay mixture and improve the density and shape stability of the molded article.
[0097] The molding step (S200) described above can be performed at an extrusion pressure of 350 to 450 MPa. Under the pressure conditions described above, the clay mixture is extruded densely, and the shape retention of the clay molded article can be improved. If the extrusion pressure is below the range described above, the clay mixture is not extruded sufficiently densely, which may result in reduced shape retention of the molded article, increased water absorption after firing, or reduced compressive strength. On the other hand, if the extrusion pressure exceeds the range described above, the residual stress of the clay molded article increases due to excessive pressure, and as a result, cracks or warping may occur during the drying or firing process. In addition, the load on the device increases, which may reduce process stability.
[0098] In the above molding step (S200), a clay mixture may be molded so that a plurality of perforations (110) penetrating in the vertical direction are formed inside the body (10) of the eco-friendly plaster brick. For example, the perforations (110) may be formed in three numbers, and the effective cross-sectional area of the load-bearing surface excluding the perforations (110) may be formed to be 70% or more of the total cross-sectional area. By forming the effective cross-sectional area to be 70% or more of the total cross-sectional area in this way, the eco-friendly plaster brick of the present invention can stably secure excellent compressive strength while securing lightness and thermal insulation properties according to the perforated structure.
[0099] For example, the eco-friendly plaster brick body (10) of the above clay molded product can be formed to have dimensions of length, width, and thickness of 190*90*57mm.
[0100] The above drying step (S300) is a step of drying the clay molded product formed in the above molding step (S200).
[0101] In the drying step (S300) above, considering that the clay molded product of this invention contains waste materials, stricter management of moisture, temperature, and ventilation conditions is required compared to general clay bricks. Specifically, in the drying step (S300), by adjusting the temperature, airflow rate, exhaust rate, and drying time so that the surface and interior of the clay molded product are dried uniformly, drying cracks, warping, and efflorescence can be suppressed.
[0102] The drying step (S300) described above may be performed in a drying chamber with a tunnel-type structure. In the drying step (S300), the clay molded products immediately after molding may first be loaded and arranged on pallets or drying racks. At this time, since the clay molded products have a high moisture content and low strength, it is desirable to load them horizontally to ensure a certain spacing between them and to prevent the load from being concentrated locally. Accordingly, sagging, deformation, or cracking of the clay molded products can be suppressed during the drying process.
[0103] After the clay molded products are loaded and arranged on a drying rack, the drying rack can be transported along the tunnel of the drying room by rail at regular intervals. Accordingly, the clay molded products can be dried step by step as they sequentially pass through multiple sections having different temperature and ventilation conditions.
[0104] The above drying chamber may include an inlet section, an intermediate section, and an outlet section. The temperature of the inlet section may be 45 to 55 ℃, the temperature of the intermediate section may be 90 to 110 ℃, and the temperature of the outlet section may be 30 to 50 ℃.
[0105] Low-temperature pre-drying can be performed in the above-mentioned inlet section. In the low-temperature pre-drying, the clay molded product is heated relatively gently, so that the rapid evaporation of moisture can be suppressed. Accordingly, the difference in the rate of moisture movement between the surface and the interior of the clay molded product is mitigated, and the occurrence of cracks due to differences in drying shrinkage can be suppressed.
[0106] Intermediate drying can be performed in the aforementioned intermediate section. During the intermediate drying, internal moisture of the clay molded product that has passed through the inlet section can be thoroughly removed. At this time, the temperature of the drying chamber can be gradually increased and the ventilation volume increased to remove moisture emitted from the clay molded product to the outside.
[0107] Final drying may be performed in the above exit section. In the above final drying, free water remaining in the clay molded product may be removed so that the clay molded product has a moisture content suitable for the subsequent firing stage. For example, the drying step may be performed until the moisture content of the clay molded product becomes 1 weight% or less. Accordingly, cracking, breakage, or rapid vaporization of moisture caused by rapid evaporation of internal moisture during the firing stage may be suppressed.
[0108] In addition, the drying step (S300) can be performed by circulating waste heat generated during the cooling step (S430) of the firing step (S400) to the drying chamber and recycling it as a drying heat source. For example, heat generated from the cooling zone of a tunnel kiln can be supplied to one side of the drying chamber by a plurality of blowers, and air containing moisture inside the drying chamber can be discharged to the other side of the drying chamber by a plurality of exhaust blowers. Accordingly, a temperature and humidity gradient can be formed inside the drying chamber along the direction of movement of the clay molded product, and the clay molded product can be dried uniformly while moving along the temperature and humidity gradient.
[0109] In this way, the present invention recycles waste heat generated during the cooling step (S430) of the firing step (S400) as a drying heat source and controls the blowing and exhaust conditions, thereby enabling stable drying of the clay molded product without using a separate heat generating device. Accordingly, the drying efficiency of the clay molded product is improved, and the fuel consumption and carbon emissions of the entire manufacturing process are reduced, thereby enhancing the eco-friendliness of the process.
[0110] The drying step (S300) is performed until the moisture content of the clay molded article becomes 1 weight% or less, and can be performed for about 83 to 85 hours. At this time, the incinerated ash-based solidifying agent can react with the moisture contained in the clay mixture during the mixing and drying process or assist in the initial bonding between the components of the clay mixture, thereby improving the drying stability of the clay molded article.
[0111] Accordingly, the clay molded product can prevent cracking, sagging, or shape deformation even with a relatively short drying time, and the drying time required to reach the target moisture content can be shortened. For example, unlike the conventional method which required about 100 to 105 hours to lower the moisture content of the clay molded product to 1 weight% or less, this invention can shorten the drying time to about 83 to 85 hours by optimizing the composition of a clay mixture containing waste heat circulation and an incineration ash-based solidifying agent.
[0112] Therefore, this invention can improve the productivity of the manufacturing process by reducing the drying process time, and can improve the energy efficiency and eco-friendliness of the manufacturing process by reducing energy and fuel consumption in the drying process.
[0113] The above firing step (S400) is a step of manufacturing eco-friendly plaster bricks by firing a dried clay molded product in a tunnel kiln. The tunnel kiln may include a preheating zone, a firing zone, and a cooling zone along the direction in which the clay molded product is transported. A preheating step (S410) is performed in the preheating zone, a main firing step (S420) is performed in the firing zone, and a cooling step (S430) is performed in the cooling zone.
[0114] The preheating step (S410) is a step of preheating the dried clay molded product before placing it into the firing table. The preheating step (S410) can be performed using the heat generated in the main firing step (S420) without separate heating. Specifically, at least a portion of the high-temperature combustion gas, radiant heat, or convective heat generated in the main firing step (S420) can be transferred to the preheating table, and accordingly, the atmosphere temperature of the preheating table can be maintained at 500 to 600 ℃. In addition, the preheating step (S410) can be performed for 7 to 8 hours.
[0115] In this way, by gradually increasing the temperature of the clay molded product during the preheating step (S410), cracking or deformation of the shape due to a rapid increase in temperature can be suppressed.
[0116] After the above preheating step (S410) is performed, the above main firing step (S420) is performed sequentially. The above main firing step (S420) is a step of forming eco-friendly plaster bricks by firing the clay molded product, and the above main firing step (S420) can be performed on the firing platform of a tunnel-type kiln. As the sintering reaction of the clay mixture components proceeds during the above main firing step (S420), the structure of the eco-friendly plaster brick can be formed densely.
[0117] In one embodiment, the firing table may include a plurality of heating control sections arranged along the direction in which the clay molded product is transported. In each heating control section, whether heating is performed or the atmosphere temperature of the firing table (hereinafter referred to as the "firing temperature") may be individually controlled. For example, the plurality of heating control sections may include a heating section where heating is performed and a non-heating section where separate heating is not performed.
[0118] The firing temperature of each heating control section included in the above heating section can be set in the range of 1050 to 1100℃, and preferably in the range of 1060 to 1080℃.
[0119] In addition, the average firing temperature of the heating section calculated based on a plurality of heating control sections included in the heating section is preferably 1070 to 1100℃, and most preferably 1070 to 1080℃.
[0120] The above heating can be performed by a burner heating method, electric heating method, radiant heating method, hot air circulation method, indirect heating method, or a combination thereof using at least one of LPG, LNG, diesel oil, heavy oil, BC oil, or biogas as fuel, and preferably by a burner heating method.
[0121] If the firing temperature in the heating section is below the above range, the sintering reaction does not proceed sufficiently, which may reduce the structural density of the eco-friendly plaster brick, and consequently, the water absorption rate may increase or the compressive strength may decrease. On the other hand, if the firing temperature in the heating section exceeds the above range, excessive sintering or liquid phase formation may cause shrinkage deviation, warping, through-hole deformation, or surface defects, and fuel consumption may increase, which may reduce the energy efficiency of the manufacturing process.
[0122] Separate heating may not be performed in the above-mentioned non-heating section. However, as the clay molded product passes through the above-mentioned non-heating section, unburned carbon contained in the unrefined fly ash may combust, thereby generating self-heating. Accordingly, the atmosphere temperature of the firing zone, i.e., the firing temperature, is maintained even in the above-mentioned non-heating section, allowing the firing reaction of the clay molded product to proceed.
[0123] Since conventional clay bricks do not contain refined fly ash, unrefined fly ash, or incinerated ash-based solidifying agents, heating must be performed throughout the entire heating control section of the firing zone without any non-heating sections to secure target physical properties. On the other hand, since the clay molded product of the present invention contains unrefined fly ash, refined fly ash, and incinerated ash-based solidifying agents, the target physical properties can be satisfied even if heating is performed only in some heating control sections and no separate heating is performed in the remaining sections.
[0124] Specifically, the heating section is the section where heating is actually performed in the firing zone, and can be performed for a total of 2 to 3 hours. That is, in this invention, through the self-heating effect of unburned carbon contained in unrefined fly ash, the tissue densification effect by refined fly ash, and the sintering assistance effect at low firing temperatures by an incinerated ash-based solidifying agent, the target physical properties of eco-friendly plaster bricks can be secured even without continuous heating throughout the entire firing zone.
[0125] Accordingly, while conventional clay bricks require heating for about 6 to 7 hours across the entire heating control section of the firing zone, this invention can reduce the actual heating time to about 2 to 3 hours. That is, by including a non-heating section in the main firing stage (S420), this invention can stably secure the water absorption rate and compressive strength of eco-friendly plaster bricks while reducing fuel consumption and manufacturing costs.
[0126] After the above-mentioned main firing step (S420), a cooling step (S430) is performed to suppress cracking and stabilize the structure of the manufactured eco-friendly plaster brick. The cooling step (S430) is a step of cooling the eco-friendly plaster brick to room temperature and can be performed in a cooling zone of a tunnel kiln.
[0127] In the above cooling step (S430), the manufactured eco-friendly plaster brick can be cooled in stages so as not to cool rapidly. Accordingly, thermal shock caused by rapid cooling after firing can be mitigated, thereby suppressing cracks or warping and improving the structural stability of the final product.
[0128] In addition, the heat generated during the cooling step (S430) can be circulated to a drying room where the drying step (S300) is performed. Accordingly, waste heat that would otherwise be discarded during the cooling process can be recycled in the drying process, and the energy efficiency of the entire manufacturing process can be improved.
[0129] In addition, to improve the surface color, texture, aesthetics, and appearance uniformity of the eco-friendly plaster brick, a glazing step (S350) of applying engobe to the surface of the dried clay molded product between the drying step (S300) and the firing step (S400) may be further performed.
[0130] The above glazing step (S350) can be performed by applying an engobe composition containing engobe raw material solids and water to the surface of the dried clay molded article, and since the details regarding the engobe are the same as those described above in the first embodiment of this invention, duplicate details are omitted below.
[0131] The concentration of the engobe used in the above glazing step (S350) may be 60 to 70 weight%. The above glazing concentration refers to the weight ratio of the solid content of the engobe raw material to the total weight of the engobe composition. If the glazing concentration is below the above range, the effect of imparting color and improving the uniformity of the appearance may not be sufficient. On the other hand, if the glazing concentration exceeds the above range, the viscosity of the engobe composition increases excessively, resulting in reduced sprayability and uneven coating thickness, aggregation, or surface defects.
[0132] The above glazing step (S350) can be performed by applying the engobe composition to the surface of the dried clay molded article. For example, it can be performed by a spray method, an immersion method, a roller coating method, a brush application method, a curtain coating method, a flow coating method, or a combination thereof, and preferably by a spray method.
[0133] For example, an engobe composition of a desired color can be stored in an engobe tank, and after connecting the engobe tank to an automatic spray gun with an engobe hose, the engobe composition can be sprayed and applied to the surface of a dried clay molded product using the automatic spray gun. Accordingly, the engobe can be uniformly applied to the surface of the clay molded product, and the surface color and texture of the eco-friendly plaster brick can be uniformly formed after firing.
[0134] Hereinafter, the specific operation and effects of the present invention will be explained through one embodiment of the present invention. However, this is presented as a preferred example of the present invention, and the scope of the rights of the present invention is not limited according to the embodiment.
[0136] [Experimental Example 1]
[0137] First, clay, weathered granite soil, kaolin, unrefined fly ash, refined fly ash, incinerated ash-based solidifying agent, and feldspar powder were mixed in the amounts shown in Table 1 below to prepare the mixture of Comparative Example 1 and Example 1.
[0138] Comparative Example 1 was prepared using a general clay brick mixture containing only clay, weathered granite soil, and kaolin. Example 1 was prepared by replacing a portion of the clay, weathered granite soil, and kaolin in the mixture of Comparative Example 1 with waste materials. The waste materials included unrefined fly ash, refined fly ash, an incineration ash-based solidifying agent, and feldspar powder, and the mixture of Example 1 was prepared to contain a total of 45% by weight of waste materials. At this time, the incineration ash-based solidifying agent used was one containing 98% Gypsum stone (CAS No. 13397-24-5), 1% by weight of Calcium sulfate hemihydrate (CAS No. 10034-76-1), and 1% by weight of Cement bonded alumina (CAS No. 65997-16-2).
[0139] Next, water was added to each mixture of clay and kneaded to prepare a clay mixture, and the moisture content of each clay mixture before molding was adjusted to approximately 15% by weight. Subsequently, each clay mixture was vacuum extruded at an extrusion pressure of 400 MPa to produce a clay molded product. The clay molded product was molded to have a length, width, and thickness of 190 mm, 90 mm, and 57 mm, respectively, and three perforations were formed in the interior that penetrate in the vertical direction. In addition, the effective cross-sectional area of the load-bearing surface, excluding the perforations, was molded to be 70% of the total cross-sectional area.
[0140] Next, each clay molded product was dried in a drying chamber with a tunnel-type structure. Specifically, each clay molded product was dried while being sequentially moved through an inlet section, an intermediate section, and an outlet section, and the temperature of the inlet section was maintained at 45–55 ℃, the temperature of the intermediate section at 90–110 ℃, and the temperature of the outlet section at 30–50 ℃. At this time, waste heat generated from the cooling zone of the firing process was circulated to the drying chamber and used as a drying heat source.
[0141] Each clay molded product was dried until the moisture content was 1 weight% or less, and the drying time required for each clay molded product to reach a moisture content of 1 weight% or less was measured and the results are shown in Table 1 below.
[0142] The above `moisture content` refers to the mass ratio of water contained in the clay molded product. A sample of 10g was taken from each clay molded product and dried in a dryer set at 105–110°C until there was no change in mass (constant weight state). Then, the moisture content was calculated using the mass of the sample before and after drying and the following Equation 2.
[0143]
[0144] Next, the firing step of each clay molded product was performed to produce the bricks of Comparative Example 1 and Example 1.
[0145] At this time, the firing stage was carried out in a tunnel kiln, and the preheating, main firing, and cooling stages were performed sequentially along the direction in which the clay molded product was transported.
[0146] In the preheating stage, direct heating using a separate LPG burner was not performed; instead, heat generated during the main firing stage and waste heat recovered during the cooling stage were utilized. Specifically, the clay molded product was preheated for approximately 7.5 hours while maintaining the ambient temperature of the preheating zone at approximately 600°C. In the cooling stage, the brick specimens fired during the main firing stage were gradually cooled to room temperature.
[0147] The main firing step was performed in a firing platform of a tunnel kiln. The firing platform included 13 heating control sections (sections 1 through 13) arranged sequentially along the direction in which the clay molded product was transported.
[0148] In Comparative Example 1, direct heating by an LPG burner was performed in all 13 heating control sections. In Comparative Example 1, the atmosphere temperature of the firing zone (firing temperature) of each heating control section was set within a temperature range of 1000 to 1180 ℃, and the average firing temperature calculated based on the 13 heating control sections was set as shown in Table 2 below. At this time, the highest firing temperature in Comparative Example 1 was 1180 ℃.
[0149] On the other hand, in the case of Example 1, direct heating by an LPG burner was performed only in sections 1 to 3 and 9 to 10 among the 13 heating control sections, and heating by an LPG burner was not performed in the remaining sections. The firing temperature of each heating control section included in the heating section of Example 1 was set within a temperature range of 1050 to 1100 ℃, and the average firing temperature of the heating section was set as shown in Table 2 below.
[0150] Subsequently, the water absorption rate and compressive strength of the brick specimens of Comparative Example 1 and Example 1 manufactured were measured according to KS L 4201, respectively, and the results are shown in Table 2 below.
[0151] According to KS L 4201, a clay brick of type 1 satisfies the quality criteria when the water absorption rate is 10% or less and the compressive strength is 24.5 MPa or more. In this experimental example, the target physical properties were evaluated as satisfying both a water absorption rate of 9% or less and a compressive strength of 26 MPa or more, which is a level superior to the standard for clay bricks of type 1 KS L 4201.
[0152] Comparative Example 1 Example 1 Ingredients (Weight%) clay 47 25.5 Masa 32 18 china clay 21 11.5 Unrefined fly ash - 35 Refined fly ash - 5 Incineration ash solidifier - 3 Jang Seok-bun - 2 Total drying time (h) 102 84
[0153] Average firing temperature (°C) LPG heating time (h) Absorption rate (%) Compressive strength (MPa) KS L 4201 Target material properties Comparative Example 1 1075 6 13.3 23.4 dissatisfaction dissatisfaction 1100 9.6 26.8 content dissatisfaction 1125 8.4 28.9 content content Example 1 1060 2.3 9.1 26.5 content dissatisfaction 1075 8.1 28.7 content content
[0154] First, as can be seen in Table 1 above, in the case of Example 1, the drying time required to reach a moisture content of 1 wt% or less was significantly shortened compared to Comparative Example 1. This is believed to be because the incinerated ash-based solidifying agent reacted with the moisture in the clay mixture to improve the bonding between raw material particles, thereby enhancing the drying stability of the clay mixture. Accordingly, cracks, sagging, and shape deformation that may occur during the drying process were suppressed, and the target moisture content could be reached in a short period of time.
[0155] Therefore, it was confirmed that the eco-friendly plaster brick of this invention, by including an incineration ash-based solidifying agent, can reduce the drying time from the existing approximately 100 hours to approximately 83 to 85 hours, and improve the productivity and energy efficiency of the drying process.
[0156] In addition, as can be seen in Table 2 above, Comparative Example 1 did not satisfy the target properties when the average firing temperature was 1075 ℃ and 1100 ℃, but satisfied the target properties when the average firing temperature was 1125 ℃.
[0157] On the other hand, in Example 1, the absorption rate did not reach the target physical properties when the average firing temperature was 1060 ℃, but excellent physical properties were exhibited when the average firing temperature was 1075 ℃. From these results, it was found that the average firing temperature is preferably 1070 to 1100 ℃, and most preferably 1070 to 1080 ℃.
[0158] In addition, although Comparative Example 1 was heated for 6 hours at an average firing temperature of 1125 ℃, Example 1 was heated for 2.3 hours at an average firing temperature of 1075 ℃, it exhibited a similar level of water absorption and compressive strength to Comparative Example 1. Accordingly, it was confirmed that Example 1 can secure equivalent physical properties even if the average firing temperature is lowered by about 50 ℃ and the actual heating time is shortened by about 3.7 hours compared to Comparative Example 1.
[0159] In addition, considering the actual operating conditions of the tunnel kiln, heat loss, and waste heat recovery conditions, a comparison of the amount of LPG used in the manufacturing process of Comparative Example 1 and Example 1 showed that in the case of Example 1, the fuel consumption was reduced by more than 40% compared to Comparative Example 1.
[0160] This is believed to be because, in Example 1, heating by the LPG burner was performed only in some of the 13 heating control sections, and in the remaining non-heating sections, the combustion heat of unburned carbon contained in the unrefined fly ash contributed to maintaining the atmosphere temperature of the calcination zone.
[0161] Such a reduction in fuel consumption can lead to a reduction in greenhouse gases and combustion emissions generated during the firing process. Therefore, it is determined that Example 1 can simultaneously improve the economic efficiency and eco-friendliness of the manufacturing process by reducing fuel consumption, energy consumption, and carbon emissions while stably securing the water absorption rate and compressive strength of the eco-friendly plaster brick.
[0163] [Experimental Example 2]
[0164] Brick specimens of Examples 1 to 4 and Comparative Examples 2 to 4 were prepared using a mixture of soil mixed with the contents of Table 3 below.
[0165] In this experimental example, the content of unrefined fly ash, incinerated ash-based solidifying agent, and feldspar powder was kept constant at 35 wt%, 3 wt%, and 2 wt%, respectively, while the content of refined fly ash was varied. At this time, the content of clay, weathered granite soil, and kaolin was adjusted according to the change in the content of refined fly ash.
[0166] Each brick specimen was manufactured by mixing, extrusion molding, drying, and firing in the same manner as in Experimental Example 1. At this time, the firing step was performed based on the conditions in Experimental Example 1 where Example 1 stably satisfied the target physical properties. Specifically, the main firing step (S420) was performed in the firing zone of a tunnel kiln, and direct heating by an LPG burner was performed only in sections 1 to 3 and sections 9 to 10 among the 13 heating control sections. At this time, the average firing temperature of the heating sections where direct heating by an LPG burner was performed was approximately 1075 ℃, and the actual LPG heating time was approximately 2.3 hours.
[0167] The water absorption rate and compressive strength of each manufactured brick specimen were measured in the same manner as in Experimental Example 1. In addition, the occurrence of efflorescence was evaluated for each brick specimen, and the results are shown in Table 3 below. The occurrence of efflorescence was evaluated by visually observing the external surface of the brick specimen, and efflorescence was assessed if white or grayish-white precipitates, stains, or powdery substances were observed on the surface.
[0169] Mixing Ingredients (Weight%) Absorption rate (%) Compressive strength (MPa) whitening clay Masa china clay Refined fly ash Comparative Example 2 27.8 19.6 12.6 0 10.3 25.7 O Comparative Example 3 26.9 19.0 12.1 2 9.4 26.1 O Example 2 26.4 18.7 11.9 3 8.9 26.8 X Example 1 25.5 18.0 11.5 5 8.1 28.7 X Example 3 25.0 17.7 11.3 6 8.6 28.9 X Example 4 24.1 17.0 10.9 8 8.8 27.4 X Comparative Example 4 23.2 16.4 10.4 10 9.2 25.8 X
[0170] As can be seen in Table 3 above, Comparative Example 2, which did not contain refined fly ash, failed to satisfy the target physical properties, and the appearance quality deteriorated due to the occurrence of efflorescence. It was determined that long-term durability and stain resistance were reduced due to the formation of moisture migration pathways or salt migration pathways. This is believed to be because, when only unrefined fly ash is used, the distribution of alkali or salt components becomes locally uneven, causing some components to migrate to the brick surface along with moisture migration during the drying or firing process.
[0171] Comparative Example 3 showed some improvement in water absorption and compressive strength compared to Comparative Example 2, but failed to satisfy the target properties as the water absorption rate exceeded 9%. In addition, whitening occurred in Comparative Example 3 as well. This is believed to be because the content of refined fly ash was insufficient, which prevented the homogenization of fly ash components within the mixture and the densification of the tissue after firing from being fully expressed.
[0172] On the other hand, Examples 1 to 4 all satisfied the target physical properties. In addition, no whitening was observed in these examples. In particular, Example 1 exhibited the lowest water absorption rate, showing the best results in terms of inhibiting moisture penetration. Furthermore, Example 3 exhibited the highest compressive strength, showing the best results in terms of mechanical strength, but the difference from the compressive strength result of Example 1 was not significant.
[0173] In Comparative Example 4, no whitening was observed, but the water absorption rate and compressive strength did not satisfy the target properties. This is believed to be because as the content of refined fly ash increased excessively, the relative content of clay-based raw materials decreased, and the balance between the self-heating effect of unrefined fly ash and the tissue stabilization effect of refined fly ash was reduced.
[0174] Therefore, it was found that in the eco-friendly plaster brick of this invention, refined fly ash is preferably included in an amount of 3 to 8 weight percent based on 100 weight percent of the total mixture, more preferably in an amount of 5 to 8 weight percent, and most preferably in an amount of 5 to 6 weight percent.
[0176] [Experimental Example 3]
[0177] Brick specimens of Examples 1 and 5 to 8 were prepared using a mixture of soil mixed with the contents of Table 4 below. In this experimental example, the total content of unrefined fly ash and refined fly ash was maintained at 40 wt%, and the FAR value was adjusted by changing the ratio of unrefined fly ash and refined fly ash.
[0178] In addition, the content of clay, weathered granite soil, kaolin, incinerated ash-based solidifying agent, and feldspar powder was maintained at 25.5 wt%, 18 wt%, 11.5 wt%, 3 wt%, and 2 wt%, respectively.
[0179] Each brick specimen was prepared by mixing, extrusion molding, drying, and firing in the same manner as in Experimental Example 3. Subsequently, the water absorption rate and compressive strength of each prepared brick specimen were measured in the same manner as in Experimental Example 3, and the occurrence of efflorescence was observed. The results are shown in Table 4 below.
[0181] Mixing Ingredients (Weight%) Absorption rate (%) Compressive strength (MPa) whitening Unrefined fly ash Refined fly ash FAR Example 5 37 3 7.5 8.8 26.5 X Example 1 35 5 12.5 8.1 28.7 X Example 6 34 6 15.0 8.5 28.8 X Example 7 33 7 17.5 8.7 28.2 X Example 8 32 8 20.0 8.9 26.9 X
[0182] As can be seen in Table 4 above, Examples 5 to 8 and Example 1 all satisfied the target properties in terms of compressive strength and water absorption. In addition, no whitening was observed in each example.
[0183] Meanwhile, Example 1 showed a result in which the water absorption rate was significantly reduced and the compressive strength was significantly improved compared to Example 5. This is believed to be because the homogenization of the fly ash components in the mixture and the densification of the brick structure after firing were more fully expressed as the relative proportion of refined fly ash increased.
[0184] In addition, Example 7 showed a significantly reduced water absorption rate and a significantly improved compressive strength compared to Example 8. This is interpreted as a result where, when the relative proportion of refined fly ash is excessively increased, the relative content of unrefined fly ash decreases, weakening the self-heating effect, and the development of sufficient strength and tissue densification are somewhat reduced under low-temperature and short-time firing conditions.
[0185] In addition, Examples 1, 6, and 7 exhibited relatively superior water absorption and compressive strength compared to other examples. In particular, Examples 1 and 6 exhibited similar levels of excellent physical properties. While the compressive strength of Example 6 was slightly higher than that of Example 1, the difference was not significant; on the other hand, Example 1 showed a lower water absorption rate compared to Example 6, making it superior in terms of inhibiting moisture penetration. Example 1 is considered to be the best composition in terms of the balance between water absorption and compressive strength, as it exhibited the lowest water absorption rate while securing sufficient compressive strength.
[0186] Therefore, it was confirmed that in the eco-friendly plaster brick of the present invention, the FAR value is preferably 7.5 to 20.0, and more preferably 12.5 to 17.5. In particular, it was found that the FAR value is most preferably 11 to 14 in terms of the balance between water absorption rate and compressive strength.
[0188] [Experimental Example 4]
[0189] A mixture of clay, weathered granite soil, kaolin, unrefined fly ash, refined fly ash, incinerated ash-based solidifying agent, and feldspar powder was prepared according to the contents of Table 5 below.
[0190] In this experimental example, the content of unrefined fly ash, refined fly ash, and feldspar powder was kept constant at 35 wt%, 5 wt%, and 2 wt%, respectively, while the content of the incineration ash-based solidifying agent was varied. At this time, the content of clay, weathered granite soil, and kaolin was adjusted so that the total mixing ratio sum was 100 wt% according to the change in the content of the incineration ash-based solidifying agent.
[0191] Brick specimens of Comparative Example 5, Comparative Example 6, Example 1, and Examples 9 to 11 were prepared using the above-mentioned mixture. Each brick specimen was prepared by mixing, extrusion molding, drying, and firing in the same manner as in Experimental Example 3.
[0192] Subsequently, the water absorption rate and compressive strength of each manufactured brick specimen were measured using the same method as in Experimental Example 3. In addition, the occurrence of drying cracks in the clay molded product during the drying process was observed, and shape deformations such as warping, dimensional deviation, or perforation deformation of the brick specimens after firing were observed. The results are shown in Table 6 below.
[0194] Mixing Soil Components (Weight%) clay Masa china clay Unrefined fly ash Refined fly ash Incineration ash solidification agent Jang Seok-bun Comparative Example 5 26.5 19 12.5 35 5 0 2 Example 9 26.5 19 11.5 1 Example 10 26.5 18 11.5 2 Example 1 25.5 18 11.5 3 Example 11 24.5 17 11.5 5 Comparative Example 6 24.5 17 10.5 6
[0195] Incineration ash-based solidifying agent (weight%) Absorption rate (%) Compressive strength (MPa) Dry cracks Shape deformation Comparative Example 5 0 9.4 26.1 O X Example 9 1 8.9 26.5 X X Example 10 2 8.7 28.0 X X Example 1 3 8.1 28.7 X X Example 11 5 8.8 27.3 X X Comparative Example 6 6 8.9 26.8 X O
[0196] As can be seen in Table 6 above, Examples 9 to 11 and Example 1 satisfied the target properties. In particular, Example 1 showed the best properties in terms of water absorption and compressive strength, and exhibited the best quality as no drying cracks or shape deformation were observed.
[0197] On the other hand, Comparative Example 5 reached the target level of compressive strength, but the water absorption rate exceeded 9% and cracks occurred during the drying process. It is believed that these drying cracks acted as internal defects after firing, which also increased the water absorption rate.
[0198] In addition, Comparative Example 6 satisfied the target properties in terms of water absorption and compressive strength, but warping of the brick body occurred after firing. This is believed to be because the bonding between raw material particles proceeded excessively locally during the firing process due to the inclusion of an excessive amount of solidifying agent. In particular, in clay bricks with a porous structure, the degree of shrinkage differs between the area around the perforations and the rest of the brick body, and it is believed that warping occurred due to this difference in the degree of local shrinkage.
[0199] From these results, it was confirmed that the incineration ash-based solidifying agent is preferably included in the mixture of this invention at 1 to 5 weight percent, and more preferably at 3 to 4 weight percent. Explanation of the symbols
[0201] 10: Eco-friendly plaster brick body 110: Perforated part
Claims
Claim 1 An eco-friendly brick manufactured by mixing a mixture of soil and water, undergoing a molding process, and then drying and firing, wherein the mixture of soil comprises clay, weathered sand, kaolin, and waste materials, and the waste materials comprise unrefined fly ash, refined fly ash, an incineration ash-based solidifying agent, and feldspar powder, and the eco-friendly brick has a plurality of cylindrical perforations (110) formed inside the body (10) of the eco-friendly brick. Claim 2 An eco-friendly plaster brick according to claim 1, wherein the perforated portion (110) is formed so as to penetrate the upper and lower parts of the eco-friendly plaster brick body (10), and the effective area of the load-bearing surface of the eco-friendly plaster brick excluding the perforated portion (110) is 70% or more of the total surface area. Claim 3 An eco-friendly plastering brick according to claim 1, wherein the mixture comprises 15-30% by weight of clay, 10-30% by weight of weathered granite, 5-15% by weight of kaolin, and 40-49% by weight of waste material. Claim 4 An eco-friendly plaster brick according to claim 1, wherein the unrefined fly ash contains 5 weight% or more of unburned carbon, and the refined fly ash contains less than 5 weight% of unburned carbon. Claim 5 An eco-friendly plaster brick according to claim 1, wherein the incinerated ash-based solidifying agent comprises dihydrate gypsum, hemihydrate gypsum, and an alumina-based inorganic binder, wherein the dihydrate gypsum is one or more selected from the group consisting of Gypsum stone (CAS No. 13397-24-5), desulfurization gypsum, and recycled gypsum, the hemihydrate gypsum is one or more selected from the group consisting of Calcium sulfate hemihydrate (CAS No. 10034-76-1), α-hemihydrate gypsum, β-hemihydrate gypsum, and calcined gypsum, and the alumina-based inorganic binder is one or more selected from the group consisting of Cement bonded alumina (CAS No. 65997-16-2), calcium aluminate cement, alumina cement, high alumina cement, and calcium aluminate. Claim 6 In claim 5, the above-mentioned incineration ash-based solidifying agent comprises 90-98% by weight of dihydrate gypsum, 1-5% by weight of hemihydrate gypsum, and 1-5% by weight of an alumina-based inorganic binder, forming an eco-friendly plaster brick. Claim 7 A mixing step (S100) for preparing a clay mixture by mixing water with a mixture of clay, weathered granite, kaolin, and waste materials; a molding step (S200) for extruding the clay mixture under vacuum to form a plurality of cylindrical perforations (110) inside an eco-friendly plaster brick body (10); and a drying step (S300) for drying the molded clay mixture. and a firing step (S400) for manufacturing eco-friendly plaster bricks by heating the dried clay molded product in a tunnel kiln; wherein the waste material includes unrefined fly ash, refined fly ash, an incineration ash-based solidifying agent, and feldspar powder; wherein the firing step (S400) comprises a preheating step (S410), a main firing step (S420), and a cooling step (S430) sequentially performed along the direction in which the clay molded product is transported in the tunnel kiln; wherein the clay molded product is preheated using heat generated in the main firing step (S420) without performing heating in the preheating step (S410); wherein the main firing step (S420) includes a heating section and a non-heating section; wherein heating is performed in the heating section so that the average firing temperature of the heating section becomes 1070~1100 ℃; wherein heating is not performed in the non-heating section and the firing reaction of the clay molded product is carried out by the combustion heat of unburned carbon contained in the unrefined fly ash A method for manufacturing eco-friendly plaster bricks, wherein the process proceeds to form eco-friendly plaster bricks, and in the cooling step (S430), the manufactured eco-friendly plaster bricks are cooled to room temperature. Claim 8 A method for manufacturing eco-friendly plaster bricks according to claim 7, wherein the mixture is a mixture of 15-30% by weight of clay, 10-30% by weight of weathered granite, 5-15% by weight of kaolin, and 40-49% by weight of waste material. Claim 9 A method for manufacturing an eco-friendly plaster brick according to claim 7, further comprising a glazing step (S350) of applying an engobe to the surface of a dried clay molded product between a drying step (S300) and a firing step (S400). Claim 10 delete
Citation Information
Patent Citations
Manufacturing methods of kaolin brick and the kaolin brick thereof
KR101200849B1
Light-weight clay bricks and pavers and method ofpreparation thereof using water-sludge
KR1020050038944A
Method for Manufacturing Antique Brick with Multilayer Coloration and Three-Dimensional Texture
KR102967407B1
Method of manufacturing clay bricks with contamination-resistance using water-sludge
KR101339911B1
Method for manufacturing clay bricks
KR1020070005816A